Pewne Nieliniowe Rozwiązywanie Dwupasowych Wstępnie Sprężonych Układów Liniowych - Łukowiak, M.; Sas, E. (Engineering Transactions, 1970)
A solution is given here of a pre-tensioned two-belt cable girder. The results of the paper are confronted in an example with the results of experimental works and other known linear solutions.